Hera : nieuwsbrief van het interprovinciaal aidscoordinaat. (Antwerpen : IPAC, 1989)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Nationalestraat 155, 2000 Antwerpen ; vanaf 04(92) 1 : Marnixplaats 16-17, 2000 Antwerpen
Nederlands
Periodiek